Measuring the effect of the North Korea-U.S. summit on the South Korean stock market - Huy Pham; Osama M. Al-Hares; Vikash Ramiah; Nisreen Moosa; Jose Fransisco Veron (Cogent Economics & Finance, 2019)
We examine the effects of the North Korea-U.S. summit and related events on the South Korean stock market over the period March 2018 to June 2018. Employing the event study methodology, we estimate sectoral abnormal returns following the events surrounding the summit and conduct several robustness tests to control for market integration and firm-specific information. Furthermore, we assess how sectoral systematic risk changes following these events by using various ARCH-type models such as GARCH, TARCH, EGARCH and PARCH. The results show that the South Korean stock market was highly sensitive to these events. In particular, we find that the market was negatively affected by the news that could reduce the probability of holding the summit and vice versa. We also find that market scepticism about the summit leads to the rise of a diamond risk structure.
Keywords: G1; G12; G14; 330; North Korea-U.S. summit; abnormal returns; event study; systematic risk